Workshop Penggunaan Aplikasi Presensi Berbasis Mobile dengan Validasi Radius Lokasi - Farida Nur Aini; Indra Listiawan (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2023)
Employee attendance is data that shows the daily attendance of employees in a company. Data that can be generated from an employee's absence is the time of arrival and departure of employees as proof of attendance at work in the office. There are several problems that arise from this finger print presence equipment. The first problem is the sensitivity of the tool, this presence tool sometimes takes a long time to recognize employee fingerprints, secondly the location of the finger print tool is too far from the employee room. The use of a Mobile-Based Presence application with Location Radius Validation is a solution to the presence problem. To facilitate the use of this presence application, it is necessary to conduct a workshop on the use of the presence application by employeesKeyword : fingerprint, presence, location